Proceedings of the 15th International Joint Conference on E-Business and Telecommunications 2018
DOI: 10.5220/0006863202210233
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy Logic based Model for Energy Consumption Trust Estimation in Electric Vehicular Networks

Abstract: Electric vehicles emerged new applications that are strongly related to the energy constraints such as the identification of the optimal path toward the vehicle's destination or toward the nearest recharging station, selection of the path where vehicle recovers extra energy, estimation of the need to recharge according to the actual battery state and the traffic state, etc. However, in electric vehicular networks, vehicles may provide wrong energy information due to sensors' failure, selfish or malicious reaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Li and Song (2016) showed that the proposed model ensures a high preciseness score regardless the network's density. Simulations in Souissi et al (2018) proved that the proposed trust model is resilient to many kinds of threats at different traffic densities. Oluoch (2015) showed that as the density goes up, the probability of detecting safety events increases simultaneously.…”
Section: Second-level: Trust Relationship Assessment For V2v and V2i mentioning
confidence: 90%
See 3 more Smart Citations
“…Li and Song (2016) showed that the proposed model ensures a high preciseness score regardless the network's density. Simulations in Souissi et al (2018) proved that the proposed trust model is resilient to many kinds of threats at different traffic densities. Oluoch (2015) showed that as the density goes up, the probability of detecting safety events increases simultaneously.…”
Section: Second-level: Trust Relationship Assessment For V2v and V2i mentioning
confidence: 90%
“…As well, the solution introduced in Li and Song ( 2016) ensures a low complexity since the adopted theory (Dempster-Shafer theory) can effectively meet with real-time applications as proved in Raya et al (2008). Regarding the fuzzy-based trust approaches, the implementation of such models is simple (Soleymani et al, 2017;Souissi et al, 2018). Simulation results presented by Hu et al (2015) show that the required time for trust estimation is high.…”
Section: Second-level: Trust Relationship Assessment For V2v and V2i mentioning
confidence: 98%
See 2 more Smart Citations
“…Although, latency and data sparsity is the major demerits of this policy [11,15,16]. Energy-related information in electric vehicular networks and a central processing entity is proposed in [20]. It discriminates between credible and erroneous values and addresses malevolent vehicles to disseminate this false information based on a fuzzy trust model.…”
Section: Related Workmentioning
confidence: 99%